PENAMPILAN BEBERAPA KARAKTER MORFOFISIOLOGI GALUR INTRODUKSI JAGUNG (Zea mays L.) YANG DISELEKSI PADA LINGKUNGAN TANAH MASAM - Khairunnisa Lubis; Surjono Hadi Sutjahjo; Muhamad Syukur; Trikoesoemaningtyas (Jurnal Pertanian Tropik, 2015)
The objective of this research was to obtain morpho-physiological characters performances maize inbreed on acid soil condition. The experiment was conducted in a Nested Design with three replications. The first factor was environment, the second factor was 16 inbreds of maize. The experiment was conducted at two environments : acid soil with criteria of Al-dd 0.2 me.100 g-1 and acid soil with criteria of Al-dd 1.87 me.100 g-1. The results showed that tolerant maize inbreed on acid soil condition had small Anthesis Silk Interval and …faster